PENINGKATAN PROGRAM KESEHATAN SEKOLAH MELALUI PEMBINAAN DOKTER KECIL PADA SISWA DI SDN 21 LIMAU SUNDAI KABUPATEN PESISIR SELATAN - Refa Rahmaddiansyah; Nurmiati Nurmiati; Sukarsi Rusti (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
The health program for school students is carried out through the School Health Business (UKS). UKS in schools has many roles, starting from increasing extracurricular activities, health education, and the skills of health workers for students. Not only for yourself but for your family, friends, and the whole school community. UKS is also expected to grow, instill, develop and guide students to always live healthy every day. This program is expected to form a Clean and Healthy Lifestyle (PHBS) for students, create a healthy school environment, and prevent students from health problems or disorders. The service activity was carried out at SDN 21 Limau Sundai, Batang Kapas District, Pesisir Selatan Regency. Activities include education about UKS, personal health and cleanliness of the school environment, healthy nutrition, immunization, disease, and treatment, basic clinical skills, and first aid in accidents. The method of educational activities carried out in the form of delivering material is in the form of lectures, health demonstrations, and case studies or practice. This is intended as an effort to promote health education in schools. The result of this activity is that the implementation of the activity went smoothly and there was great support from the school, as well as extraordinary enthusiasm from the little doctor who was fostered. This service program runs well and smoothly and is expected to improve Clean and Healthy Life Behavior for students of SDN 21 Limau Sundai, both within the school and outside of school.